Pro-Health Behaviours and Depressive Symptoms as Well as Satisfaction with and Quality of Life Among Women with Hashimoto’s Disease - Maria Gacek; Agnieszka Wojtowicz; Jolanta Kędzior (European Journal of Investigation in Health, Psychology and Education)
Background: Lifestyle is one of the important factors determining health and quality of life. The aim of the study was to analyse relationships between pro-health behaviours, depression and quality of life among women with Hashimoto’s thyroiditis. Material and methods: The study was conducted among 219 women aged 20–50 from southern Poland, using (i) Juczyński’s Healthy Behaviour Inventory (HBI); (ii) Beck’s Depression Inventory (BDI); (iii) satisfaction with life scale (SWLS) and (iv) WHOQoL-Bref (Quality of Life-BREFF). In the statistical analysis, Spearman’s R correlation coefficient and multiple regression analysis were applied, assuming a significance level of α = 0.05. Results: It was shown that with the increase in the general indicator of pro-health behaviours, the level of depressive symptoms decreased, while the level of satisfaction with life and all four aspects of quality of life on the WHOQoL scale increased (p < 0.001). Regression analysis demonstrated that the model consisting of all analysed pro-health behaviours explains a high percentage of variance in depressive symptoms (38%), life satisfaction (31%) and all aspects of quality of life, including those somatic and social (19%), psychological (28%) and environmental (12%). Conclusions: The noted correlations between pro-health behaviours, the intensity of depressive symptoms as well as the level of life satisfaction and quality of life indicate justification for promoting a pro-health lifestyle as a significant factor contributing to mental health and better quality of life among women with hypothyroidism.